MENINGKATKAN BERPIKIR KRITIS DALAM MENENTUKAN POKOK PIKIRAN MENGGUNAKAN KOMBINASI MODEL PROBLEM BASED LEARNING, THINK PAIR SHARE, DAN SNOWBALL THROWING DI SDN PELAMBUAN 2 BANJARMASIN - Olfah, Maria; Mahmuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning activity, the ability to think critically in determining the main thoughts, and the learning outcomes of 5th grade students of SDN Pelambuan 2 Banjarmasin in Indonesian learning. Learning tends to be boring, one-way, and makes less use of varied learning models and media. This research aims to improve student activities, critical thinking skills, and learning outcomes through the application of a combination of Problem Based Learning (PBL), Think Pair and Share (TPS) and Snowball Throwing models. This research is a Class Action Research (PTK) with a qualitative approach that was carried out for four meetings. The subject of the study was 19 5th grade students in the even semester of the 2024/2025 school year. Data were collected through observation of teacher and student activities, as well as critical thinking skills and written tests for learning outcomes. teacher activity reached a score of 30 (Very Good), student activity was 84% (Very Active), students' critical thinking ability was 84% (Highly Skilled), and the completeness of student learning outcomes classically reached 89%. Thus, the application of the PBL model in combination with TPS and Snowball Throwing has proven to be effective in improving the quality of the overall learning process.